2021
DOI: 10.3390/cells10112910
|View full text |Cite
|
Sign up to set email alerts
|

Protein Binding to Cis-Motifs in mRNAs Coding Sequence Is Common and Regulates Transcript Stability and the Rate of Translation

Abstract: Protein binding to the non-coding regions of mRNAs is relatively well characterized and its functionality has been described in many examples. New results obtained by high-throughput methods indicate that binding to the coding sequence (CDS) by RNA-binding proteins is also quite common, but the functions thereof are more obscure. As described in this review, CDS binding has a role in the regulation of mRNA stability, but it has also a more intriguing role in the regulation of translational efficiency. Global a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, K d values previously reported for HAX1 binding to 3'UTR are lower (Sarnowska et al 2007), indicating different strength of interaction and, possibly, different mode of binding for CDS and 3'UTR regions. Similar phenomenon was also observed for GLD-1 and FMRP proteins, involved in the regulation of translation (Grzybowska and Wakula 2021).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Interestingly, K d values previously reported for HAX1 binding to 3'UTR are lower (Sarnowska et al 2007), indicating different strength of interaction and, possibly, different mode of binding for CDS and 3'UTR regions. Similar phenomenon was also observed for GLD-1 and FMRP proteins, involved in the regulation of translation (Grzybowska and Wakula 2021).…”
Section: Discussionsupporting
confidence: 81%
“…However, new high-throughput analyzes demonstrated that binding to the CDS is not as uncommon as previously thought and may have a role in the regulation of mRNA stability (Grzybowska and Wakula 2021). Interestingly, this stabilization should refer to the situation when mRNA is not actively translated, thus it is not covered and protected by ribosomes and susceptible to endonuclease attack, like in case of protein CRD-BP, which binds to c-myc mRNA, protecting it (Lemm and Ross 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[2] Secondary structures within coding sequence mainly impact the speed of transcription and splicing (including alternative splicing), though they can also influence transport and translation. [3][4][5] Secondary structures to maintain mRNA stability might be present, presumably, in all parts of the transcript. [3,4,6] 3′ UTRs include cis-elements implicated in a range of functions including: translational regulation, subcellular localization, and stability.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Secondary structures to maintain mRNA stability might be present, presumably, in all parts of the transcript. [3,4,6] 3′ UTRs include cis-elements implicated in a range of functions including: translational regulation, subcellular localization, and stability. [7] In humans, the average length of 3′ UTRs is 1028 nt, [8] whereas in yeast, it is 144 nt.…”
Section: Introductionmentioning
confidence: 99%